2016
DOI: 10.1039/c5sm02350e
|View full text |Cite
|
Sign up to set email alerts
|

Micro-phase separation in two dimensional suspensions of self-propelled spheres and dumbbells

Abstract: We use numerical simulations to study the phase behavior of self-propelled spherical and dumbbellar particles interacting via micro-phase separation inducing potentials. Our results indicate that under the appropriate conditions, it is possible to drive the formation of two new active states; a spinning cluster crystal, i.e. an ordered mesoscopic phase having finite size spinning crystallites as lattice sites, and a fluid of living clusters, i.e. a two dimensional fluid where each "particle" is a finite size l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Non-doped clusters do not rotate. In this respect, our system differs from simulations of dumbbell aggregates [53,54] and studies of bacterial micro-rotors [55], where rotation is caused by the random addition of individual torques and there is no global chirality in the system.…”
Section: Discussionmentioning
confidence: 83%
“…Non-doped clusters do not rotate. In this respect, our system differs from simulations of dumbbell aggregates [53,54] and studies of bacterial micro-rotors [55], where rotation is caused by the random addition of individual torques and there is no global chirality in the system.…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that repulsive active rods exhibit a phaseseparated state characterized by the formation of polar clusters [32]. Similarly, dilute suspensions of active dumbbells form rotating clusters when particles interact both via a short-range attraction and long-range repul-sion [28] and an isotropic attraction [33], in the latter case displaying a nematic order with spiral patterns in two dimensions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by experiments on dilute suspensions of colloids [35] and bacteria [33], showing cluster formation, and motivated by understanding how hydrodynamics could affect the formation of living clusters [27,28,36], we have carried out a systematic numerical analysis on dilute 2D suspensions of attractive self-propelled spheres both in the presence (wet active system) and absence (dry active system) of hydrodynamic interactions [37]. We identify the conditions at which the system forms clusters, and characterize their morphology considering and neglecting hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…One of the simplest models of active matter is monodisperse sterically interacting disks undergoing active Brownian motion or run and tumble dynamics. These can transition from a uniform liquid state to a clump or phase separated state with increasing disk density, increasing persistence length [15][16][17][18][19][20] or increasing run length [21][22][23] . In the phase separated regime, which appears even in the absence of an attractive component in the particle-particle interactions, large clumps of densely packed disks are separated by a low density gas of active particles.…”
Section: Introductionmentioning
confidence: 99%